2009
DOI: 10.1080/09603120802527646
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing workers to follow food safety management systems in meat plants in Ontario, Canada

Abstract: Small and medium sized food businesses have been slow to adopt food safety management systems (FSMSs) such as good manufacturing practices and Hazard Analysis Critical Control Point (HACCP). This study identifies factors influencing workers in their implementation of food safety practices in small and medium meat processing establishments in Ontario, Canada. A qualitative approach was used to explore in-plant factors that influence the implementation of FSMSs. Thirteen in-depth interviews in five meat plants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…There are numerous definitions of small and medium sized enterprises (Ball et al, 2009;European Commission, 2003;Loecher, 2000).…”
Section: Plant Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous definitions of small and medium sized enterprises (Ball et al, 2009;European Commission, 2003;Loecher, 2000).…”
Section: Plant Selectionmentioning
confidence: 99%
“…Various studies have shown socio-psychological factors to influence the implementation of HACCP programs (Ball, Wilcock, & Aung, 2009;Ball, Wilcock, & Aung, 2010;Clayton & Griffith, 2008;Gilling et al, 2001;Hinsz, Nickell, & Park, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This study concluded that more knowledge-based interventions should be implemented for HACCP team members. Ball, Wilcock, and Aung (2009) identified three themes that potentially present barriers to compliance with food safety management systems and proposed a model to describe factors that influence food safety behaviors, which is subjected to further validation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Procedures guide workers through their production and sanitation activities, preventing poor decision making (5,34). For preventive measure design, a significant difference (P < 0.05) between clusters was only observed in specificity of sanitation programs.…”
Section: Resultsmentioning
confidence: 96%